Interactions Between Acidic (Al3+, Fe2+) and Basic (Ca2+, Mg2+) Cations in Oxisol and Ultisol under Acidification Induced by Simulated Acid Rain - Nawaz, Rab; Arshad, Muhammad; Shahzad Sarfraz, Muhammad; Waseem Ashraf, Muhammad; Umar Hayyat, Muhammad; Mahmood, Rashid; Parkpian, Preeda (Asian Journal of Chemistry, 2014)
This study focuses on the interactions of aluminum and iron with exchangeable bivalent base cations (Ca2+ and Mg2+) at different acidity levels in soils treated with acidic solutions. Acidic (pH 5.0, 4.0, 3.5, 3.0, 2.5, 2.0) and non-acidic (7, control) solutions were applied to the soil columns for 45 days representing average annual rainfall. Soil samples from different depths were analyzed for soil pH (acidity) and target elements (Ca2+, Mg2+, Al3+ and Fe2+). The extractable aluminum and iron increased with a decrease in the concentration of exchangeable calcium and magnesium as the soil pH drops to 5 or low particularly in the upper layers of the investigated soils. The concentrations of soluble base cations increased as soil pH became moderately acidic and decreased as soil pH became highly acidic. However, concentration of exchangeable base cations decreased at higher levels of acidity due to accelerated transformations of exchangeable forms into soluble ones.